De-centering queer theory : Communist sexuality in the flow during and after the Cold War - Popa, Bogdan (Book collections on Project MUSE., 2021)
De-centering queer theory seeks to reorient queer theory to a different conception of bodies and sexuality derived from Eastern European Marxism. The book articulates a contrast between the concept of the productive body, which draws its epistemology from Soviet and avant-garde theorists, and Cold War gender, which is defined as the social construction of the body. The first part of the book concentrates on the theoretical and visual production of Eastern European Marxism, which proposed an alternative version of sexuality to that of western liberalism. In doing so it offers a historical angle to understand the emergence not only of an alternative epistemology, but also of queer theory's vocabulary. The second part of the book provides a Marxist, anti-capitalist archive for queer studies, which often neglects to engage critically with its liberal and Cold War underpinnings.